An adhesive bonding approach by hydrogen silsesquioxane for silicon carbide-based LED applications. (1st March 2019) - Lin, Li; Ou, Yiyu; Jokubavicius, Valdas; Syväjärvi, Mikael; Liang, Meng; Liu, Zhiqiang; Yi, Xiaoyan; Schuh, Philipp; Wellmann, Peter; Herstrøm, Berit; Jensen, Flemming; Ou, Haiyan
Abstract: We report an adhesive bonding approach using hydrogen silsesquioxane (HSQ) for silicon carbide (SiC) samples. A hybrid light-emitting diode (LED) was successfully fabricated through bonding a near-ultraviolet (NUV) LED grown on a commercial 4H-SiC substrate to a free-standing boron-nitrogen co-doped fluorescent-SiC epi-layer. The bonding quality and the electrical performance of the hybrid LED device were characterized. Neither voids nor defects were observed which indicates a good bonding quality of the proposed HSQ approach. A strong warm white emission was successfully obtained from the hybrid LED through an electric current injection of 30 mA.